2019
DOI: 10.1186/s13046-019-1054-x
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L activated by mutant p53 and Egr-1 promotes ionizing radiation-induced EMT in human NSCLC

Abstract: BackgroundIonizing radiation (IR) is one of the major clinical therapies of cancer, although it increases the epithelial-mesenchymal transition (EMT) of non-small cell lung cancer (NSCLC), unexpectedly. The cellular and molecular mechanisms underlying this role are not completely understood.MethodsWe used NSCLC cell lines as well as tumor specimens from 78 patients with NSCLC to evaluate p53, Cathepsin L (CTSL) and EMT phenotypic changes. Xenograft models was also utilized to examine the roles of mutant p53 (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…This would suggest that, in parasitized DCs, migratory responses are maintained while activation is suppressed or down-modulated (Figure 9). In line with this, recent reports show that Egr-1 responses promote epithelial-mesenchymal transition (EMT) and metastasis in malignancies (Shao et al, 2018; Wang et al, 2019). T. gondii encounters DCs in peripheral tissues, such as the intestine, and DCs function as shuttles (“Trojan horse”) that potentiate the systemic dissemination of the parasite (Courret et al, 2006; Lambert et al, 2006; Bierly et al, 2008).…”
Section: Discussionmentioning
confidence: 58%
“…This would suggest that, in parasitized DCs, migratory responses are maintained while activation is suppressed or down-modulated (Figure 9). In line with this, recent reports show that Egr-1 responses promote epithelial-mesenchymal transition (EMT) and metastasis in malignancies (Shao et al, 2018; Wang et al, 2019). T. gondii encounters DCs in peripheral tissues, such as the intestine, and DCs function as shuttles (“Trojan horse”) that potentiate the systemic dissemination of the parasite (Courret et al, 2006; Lambert et al, 2006; Bierly et al, 2008).…”
Section: Discussionmentioning
confidence: 58%
“…The transcription factor p53 is known to control radiation sensitivity [25,26,27,28]. Except in a few reports, p53 dysfunction has been shown to correlate with reduced radiosensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…As a member of the early gene family, Egr-1 has an important role in drug resistance in cancer cells and could regulate the expression of CTSL [2427]. Previous studies in our laboratory have indicated that Egr-1 may be the target protein of mut-p53 in regulating CTSL mediated EMT under IR in NSCLC [40]. We indicated here that Egr-1 regulated CTSL-mediated cisplatin resistance in lung cancer by affecting the activity of CTSL promoter.…”
Section: Discussionmentioning
confidence: 99%